2014
DOI: 10.1155/2014/430832
|View full text |Cite
|
Sign up to set email alerts
|

Workplace-Related Traumatic Injuries: Insights from a Rapidly Developing Middle Eastern Country

Abstract: Traumatic workplace-related injuries (WRIs) carry a substantial negative impact on the public health worldwide. We aimed to study the incidence and outcomes of WRIs in Qatar. We conducted occupational injury surveillance for all WRI patients between 2010 and 2012. A total of 5152 patients were admitted to the level 1 trauma unit in Qatar, of which 1496 (29%) sustained WRI with a mean age of 34.3 ± 10.3. Fall from height (FFH) (51%) followed by being struck by heavy objects (FHO) (18%) and motor vehicle crashes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 16 publications
(31 reference statements)
9
47
0
Order By: Relevance
“…The global construction sector is the most hazardous for occupational accidents/injuries, with extensive involvement of migrant workers. It has been shown that migrant workers in the construction sector have a significantly high proportion (42%) of severe occupational injuries, which is consistent with our study (18). After construction, trade and manufacturing economic activities were the second and third most problematic groups, respectively, regarding incidence of occupational injuries/diseases among NSIWs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The global construction sector is the most hazardous for occupational accidents/injuries, with extensive involvement of migrant workers. It has been shown that migrant workers in the construction sector have a significantly high proportion (42%) of severe occupational injuries, which is consistent with our study (18). After construction, trade and manufacturing economic activities were the second and third most problematic groups, respectively, regarding incidence of occupational injuries/diseases among NSIWs.…”
Section: Discussionsupporting
confidence: 91%
“…The increased trend in occupational injuries for SIWs and NSIWs among industrial, chemical and food workers could have been due to inadequate preventive measures. A recent study reported that occupational injuries among migrant workers were due to stress and depression, which may have been due to job choice and being away from their home country (18). Trends in occupational injuries/diseases increased in Saudi and non-Saudi technicians.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that more than one out of three (32%) trauma admissions were fall-related, poses a significant impact on the health financial system in the country. It was demonstrated that 95% of the fall injuries in Qatar were work-related [15] and half of the total injuries at work-place were due to falls [2]. Working age group with a mean age of 33 years and males were the main principal victims [15].…”
Section: Discussionmentioning
confidence: 99%
“…Males were predominant (89%), more likely to fall at workplace, fall from a greater height and experience polytrauma than females. Working age-group (20-59 years) were the major victims (73%), more likely to fall at work place, fall from height comparing to older adults who tend to fall at home, fall from the Epidemiology of fall-related injuries in Qatar remains understudied, however some hospital-based studies on moderate to severe injuries suggest that FFH was the key contributor for work-related injuries (nearly 50%), particularly among the 18-59 age group (97%) [2]. Incidence of fall-related injuries was estimated as 86.7 per 100,000 workers with a mortality rate of 8.44 per 100,000 workers costing over 4.4 million USD, with an average cost of 15,735 USD per patient which is in fact costs 15 times higher than in the United States (1,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation